From Purification to Resilience: The Qur’anic Concept of Tazkiyat al-Nafs and Its Relevance to Generation Z Mental Challenges in Islamic Boarding Schools - Al Hafizh, Fauzan; Ramadhani, Wali; At-Tijjani, Mubarak (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2026)
Generation Z students in Islamic boarding schools (pesantren) increasingly face complex mental challenges such as anxiety, emotional instability, and a sense of meaninglessness. These issues are intensified by academic pressures, digital culture, and identity transitions. Addressing such problems requires a Qur’anic framework that provides both spiritual guidance and practical solutions. This study aims to explore the Qur’anic concept of Tazkiyat al-Nafs as a spiritual strategy to overcome mental challenges among Generation Z in pesantren, and to evaluate its relevance in fostering resilience, self-discipline, and stable spirituality. Employing Abdul Hayy al-Farmawi’s thematic exegesis (Tafsir Maudhu’i), this research adopts a qualitative case study design at Ma’had Daarul Qur’an Langsa. Data were collected through textual analysis of Qur’anic verses related to purification, struggle (mujahadah), patience, gratitude, sincerity, and piety, complemented by in-depth interviews and direct observation of students and teachers. Data analysis involved reduction, categorization, and thematic interpretation. Findings reveal that Qur’anic principles effectively address Gen-Z mental challenges. Tazkiyat al-Nafs purifies the soul from negative traits; Mujahadah cultivates discipline; patience and gratitude strengthen resilience; while sincerity and piety establish stable spirituality. These practices reduce anxiety, enhance emotional regulation, and restore meaning in students’ lives. The Qur’anic concept of Tazkiyat al-Nafs is relevant and applicable to the mental challenges of Generation Z in pesantren. Integrating thematic exegesis into pesantren education is recommended as a holistic approach to reinforce students’ mental and spiritual well-being. Generasi Z yang menempuh pendidikan di pesantren menghadapi tantangan mental yang semakin kompleks, seperti kecemasan, instabilitas emosi, dan krisis makna akibat tekanan akademik, pengaruh budaya digital, serta transisi identitas. Kondisi ini menuntut pendekatan Qur’ani yang mampu memberikan solusi spiritual sekaligus praktis untuk memperkuat kesejahteraan mental santri. Penelitian ini bertujuan mengeksplorasi konsep Qur’ani Tazkiyat al-Nafs sebagai strategi spiritual dalam mengatasi problem mental Generasi Z di pesantren, serta menilai relevansinya terhadap pembentukan resiliensi, disiplin diri, dan stabilitas spiritual. Penelitian menggunakan pendekatan tafsir tematik (Tafsir Maudhu’i) Abdul Hayy al-Farmawi dengan desain kualitatif studi kasus di Ma’had Daarul Qur’an Langsa. Data dikumpulkan melalui analisis ayat-ayat Qur’an terkait tazkiyah, mujahadah, sabar, syukur, ikhlas, dan taqwa, serta wawancara mendalam dan observasi langsung terhadap santri dan ustadz. Analisis dilakukan dengan teknik reduksi, kategorisasi, dan interpretasi tematik. Temuan menunjukkan bahwa konsep Qur’ani mampu menjadi solusi atas problem mental Gen-Z. Tazkiyat al-Nafs berfungsi sebagai purifikasi jiwa dari sifat negatif; Mujahadah melatih disiplin diri; sabar dan syukur menjadi strategi resiliensi; serta ikhlas dan taqwa membentuk fondasi spiritualitas yang stabil. Praktik ini terbukti menurunkan kecemasan, meningkatkan kontrol emosi, dan memperkuat rasa makna hidup santri. Konsep Qur’ani Tazkiyat al-Nafs relevan dan aplikatif dalam menjawab tantangan mental Generasi Z di pesantren. Integrasi tafsir tematik dengan pendidikan pesantren direkomendasikan sebagai pendekatan holistik untuk memperkuat kesejahteraan mental dan spiritual santri.